Tax evasion by business income taxpayers in Klang Valley Malaysia - Wee@Alan Wee, Ching Hua (2020)
Income tax is one of the major sources of revenue for Malaysian government. It has become an essential tool for the implementation of various government policies aimed at improving the welfare of the citizens and the development of the country. Tax evasion is alarming in Malaysia as more stringent measures are employed by Inland Revenue Board Malaysia (IRBM) to tackle this existing concerns. In general, tax is an illegal act of non-payment or under payment of tax. Although many studies on tax evasion were carried out in the past, there are still limited studies that used proprietary tax audit data to identify the association between taxpayers’ characteristics and tax evasion. Hence, this study will determine the significant difference between gender, age, business size and income level with tax evasion especially among taxpayers with business income in Klang Valley, Malaysia which has been identified to have low compliance rate in year assessment 2018. This study also employs actual data on the understatement of income as a proxy in measurement of tax evasion. The result shows that gender and income level have significant difference with tax evasion while age and business size have no significant difference with tax evasion. The result of this study are highly relevant to IRBM in developing strategies to curb tax evasion as well as add value to the current works on literature related to taxation.